PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS TERHADAP HASIL BELAJAR EKONOMI - Savitri, Radia; Wahyuni, Sri; Areva, Desi (Pendidikan Ekonomi, 2013)
Abstract: This research is motivated by the results of the economic study mid second semester exams of class X students of SMAN 7 Padang Academic Year 2012/2013 is still low under minimum completeness criteria . This study aims to determine whether the results of the economic study of students who apply cooperative learning model TPS is higher than the results of the economic study of students who apply conventional teaching class X SMAN 7 Padang . This type of research is experimental . The study population was a tenth grade students of SMAN 7 Padang Academic Year 2012/2013 . Based on economic achievement test scores of students , the average values obtained experimental class and control class 68.13 76.15 . Z - test analysis results , obtained Zhitung ( 47.18 ) > Ztabel ( 1.645 ) which means that the hypothesis is accepted . From this study it can be concluded that the results of the economic study of students who use cooperative learning model TPS higher than the students who apply conventional teaching class X student of SMAN 7 Padang . To the researchers suggested that teachers especially teachers of SMAN 7 Padang economic and high school teachers in general to implement cooperative learning model TPS as an alternative learning model that can be used to improve student learning outcomes . And to researchers who are interested are advised to conduct advanced research in different materials .Key Words: Think Pair Share Cooperative Methode, Economic Study Results